Generalized measures of wage differentials - Philippe Van Kerm (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper considers new distributionally sensitive summary measures of wage differentials, not solely determined by the average wage of the average person but by differences across complete wage distributions. Considerations of risk or inequality aversion in the assessment of wage differentials are explicitly included, transplanting expected utility concepts familiar to income distribution analysts. In an application to the gender pay gap in Luxembourg the disadvantage of women persists with the new generalized measures of wage differentials. This suggests that lower average wages for women are not compensated by less dispersed distributions. The paper also illustrates original estimation of wage distributions in the presence of covariates and under endogenous labour market participation.
Keywords: 330